Bone angiocrine factors - Ribatti, Domenico; d’Amati, Antonio (Frontiers in Cell and Developmental Biology, 2023)
Angiogenesis in the bone is unique and involves distinctive signals. Angiogenesis occurs during the creation of endochondral bone and is mediated by a variety of cells and factors. An initially avascular cartilage template is invaded by blood vessels from the nearby subchondral bone thanks to the secreted angiogenic chemicals by hypertrophic chondrocytes. Vascular endothelial growth factor (VEGF), one of several angiogenic molecules, is a significant regulator of blood vessel invasion, cartilage remodeling, and ossification of freshly created bone matrix; chondrocyte proliferation and hypertrophy are facilitated by the production of VEGFA and VEGFR-2, which is stimulated by FGF). NOTCH signaling controls blood capillaries formation during bone maturation and regeneration, while hypoxia-inducible factor 1 alpha (HIF1-a) promotes chondrocyte development by switching to anaerobic metabolism. To control skeletal remodeling and repair, osteogenic cells release angiogenic factors, whereas endothelial cells secrete angiocrine factors. One of the better instances of functional blood vessels specialization for certain organs is the skeletal system. A subpopulation of capillary endothelial cells in the bone regulate the activity of osteoprogenitor cells, which in turn affects bone formation during development and adult homeostasis. Angiogenesis and osteogenesis are strictly connected, and their crosstalk is essential to guarantee bone formation and to maintain bone homeostasis. Pathological processes including inflammation, cancer, and aging include both bone endothelial cells and angiocrine factors. The study and understanding of these mechanisms is fundamental, because molecules and factors involved in these mechanisms may represent key targets for novel and advanced therapies.